KEPUASAN KONSUMEN DI AMANAH OPTIKAL SUMEDANG - Karana, Indra; Nugroho, Anggit; Luthfiah, Saarah (stikes dharma husada bandung, 2022)
Optics is a facility that provides services for eye examinations, refractive examinations and services for correcting glasses and or contact lenses. In this case, optics must always pay attention to the needs and desires of consumers and try to meet consumer expectations by providing services. Every optic is required to make consumers feel satisfied by providing better offers and services. The purpose of this study was to determine customer satisfaction based on; product quality, emotional quality, and the suitability of the price of goods. The research method uses quantitative descriptive techniques with the object of research at Amanah Optik Sumedang. Research results based on; the product quality is categorized as quite satisfactory, the service quality is quite satisfactory, the emotional factor is quite satisfactory, and the price suitability is quite satisfactory. Customer satisfaction based on service quality must be improved in terms of speed and responsiveness, good communication in providing services to consumers can provide convenience in consulting. Improved physical facilities, especially comfortable waiting rooms and adequate parking facilities can make consumers feel comfortable and calm when visiting